Reseña de Gentner, D. y Goldin-Meadow, S. (eds.) (2003). Language en Mind. Advances in the Study og Language and Thought. - Lozano Lubián, Antonio (Pragmalingüística, 2011)
<!--[if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> Se trata de una reseña de Gentner, D. y Goldin-Meadow, S. (eds.) (2003). Language in Mind. Advances in the Study of Language and Thought.